Improving Students' Learning Outcomes with The Set Method on Sound Material in Class 4 SDN Kutasari 5 - M. Ilham Rahman Riyadi; Alwi Sofyan (International Journal of Science and Applied Science: Conference Series, 2021)
This study aims to improve student learning outcomes using the Student Engagement Time (SET) method on Sound material in grade 4 SDN Kutasari 5. The SET method is an active learning method that encourages students to be actively involved in the learning process by providing time for reflection and asking questions answer in class. This study used a classroom action approach with a cycle design consisting of two learning cycles. Research participants were grade 4 students at SDN Kutasari 5, totaling 20 students. Data collection was carried out using formative tests and observations. Data were analyzed using a qualitative descriptive analysis. The results of the study show that the use of the SET method can improve student learning outcomes in Sound material. Improved learning outcomes can be seen in the indicators of understanding concepts, process skills, and scientific attitudes. The average value of formative tests in cycle I was 71.5 and increased to 83.5 in cycle II. In conclusion, it can be concluded that the use of the SET method can improve student learning outcomes in Sound material in class 4 SDN Kutasari 5. Suggestions for further research are the use of the SET method can be developed with a wider variety of learning techniques and strategies to improve student learning outcomes on different materials.